Estuary planning and management: the case of Vouga Estuary (Ria de Aveiro), Portugal - Fidélis, Teresa
Estuarine areas often concentrate complex and conflicting sets of natural, economic and social resources and activities with multiple challenges to planning and management approaches as well as to governance practices. Using a set of integration factors depicted from the literature review, the paper analyzes the main features of the new set of the Portuguese estuary types of plans and assesses their potential added value, while focusing the analysis on the estuary of the Vouga River (Ria de Aveiro). The results are twofold. On the one side, their uniqueness, by treating the estuary as a planning unit, integrating the water resources and the land use planning systems and by establishing mandatory rules for the estuary uses, embodies relevant potential for reducing boundary tensions and to improve integrative approaches. On the other side, while at the level of plan content the contribution of the Portuguese Estuary Land Use and Management Plans (Planos de Ordenamento de Estuário) legislation brings strong new prospects for integration, at the level of planning process and implementation, further efforts should be undertaken. Their added value, especially in complex institutional and societal estuarine contexts, such as the Ria de Aveiro, strongly depends on more robust participation schemes through which knowledge, institutions, aims and measures are articulated in a collective vision and shared governance process.